A novel bismuth-based metal-organic framework for high volumetric methane and carbon dioxide adsorption - Savage, Mathew; Yang, Sihai; Suyetin, Mikhail; Bichoutskaia, Elena; Lewis, William; Blake, Alexander J.; Barnett, Sarah A.; Schröder, Martin (Wiley-VCH Verlag, 2014)
Solvothermal reaction of H4L (L = biphenyl-3,3’,5,5’-tetracarboxylate) and Bi(NO3)3·(H2O)5 in a mixture of DMF/MeCN/H2O in the presence of piperazine and nitric acid at 100 oC for 10 h affords the solvated metal-organic polymer [Bi2(L)1.5(H2O)2]·(DMF)3.5·(H2O)3 (NOTT-220-solv). A single crystal X-ray structure determination confirms that it crystallises in space group P2/c and has a neutral and non-interpenetrated structure comprising binuclear Bi2 centres bridged by tetracarboxylate ligands. NOTT-220-solv shows a 3,6-connected network having a new framework topology with a {4·62}2{42·65·88}{62·8} point symbol. The desolvated material NOTT-220a shows exceptionally high adsorption uptakes for CH4 and CO2 on a volumetric basis at moderate pressures and temperatures with a CO2 uptake of 553 gL-1 (20 bar, 293 K) with a saturation uptake of 688 gL-1 (1 bar, 195 K). The corresponding CH4 uptake of 165 V(STP)/V (20 bar, 293 K) and 189 V(STP/V) (35 bar, 293 K) is within the top three MOF materials under the same conditions, surpassed only by PCN-14 and Ni-MOF-74 (230 and 190 V(STP)/V 35 Bar, 298 K). The maximum CH4 uptake for NOTT-220a was recorded at 20 bar and 195 K to be 287 V(STP)/V, while H2 uptake of NOTT-220a at 20 bar, 77 K is 42 gL-1. These gas uptakes have been modelled by Grand Canonical Monte Carlo (GCMC) and Density Functional Theory (DFT) calculations, which confirm the experimental data and give insights into the nature of the binding sites of CH4 and CO2 in this porous hybrid material.